Cu(ii) immobilized on Fe3O4@HNTs–tetrazole (CFHT) nanocomposite: synthesis, characterization, investigation of its catalytic role for the 1, 3 dipolar cycloaddition reaction, and antibacterial activity. Issue 44 (15th July 2020) - Hajizadeh, Zoleikha; Hassanzadeh-Afruzi, Fereshte; Jelodar, Diana Fallah; Ahghari, Mohammad Reza; Maleki, Ali
Abstract : In the present study, Cu(ii ) immobilized on an Fe3 O4 @HNTs–tetrazole (CFHT) nanocomposite was designed and prepared. Abstract : In the present study, Cu(ii ) immobilized on an Fe3 O4 @HNTs–tetrazole (CFHT) nanocomposite was designed and prepared. For this, halloysite nanotubes (HNTs) as natural mesoporous substances were modified during several chemical reactions. The synthesis of the CFHT nanocomposite was investigated step by step with the required physicochemical techniques such as FT-IR, EDX, SEM, TEM, XRD, VSM, TGA and CHNS analyses. After ensuring that the nanocomposite was successfully prepared, its catalytic application in the synthesis of the 5-substituted 1 H -tetrazole derivatives via multicomponent reactions (MCRs) between aromatic aldehydes, malononitrile, and sodium azide was assessed. According to the experimental results, the prepared nanocomposite exhibited excellent capability for conducting this MCR reaction. All desired products were obtained in a short reaction time (30–40 min) with high productivity (90–97%) and without a complicated workup procedure. Furthermore, the magnetic property of the synthesized heterogeneous nanocomposite empowers it to be recovered and reused in five times successive reactions without any significant reduction in reaction efficiency. Moreover, the remarkable antibacterial activity of the nanocomposite against Escherichia coli ( E. coli ) and Staphylococcus aureus ( S. aureus ) was evaluated by agar diffusion and plate-count methods. The zones of inhibition were around 16 and 20 mm for E. coli and S. aureus bacteria, respectively. Also, colony analysis confirms the killing of bacteria by using the CFHT nanocomposite.